2020
DOI: 10.3389/fneur.2020.586606
|View full text |Cite
|
Sign up to set email alerts
|

Do We Belittle Essential Tremor by Calling It a Syndrome Rather Than a Disease? No

Abstract: A task force of the International Parkinson and Movement Disorder Society (MDS) recently published a tremor classification scheme that is based on the nosologic principle of two primary axes for classifying an illness: clinical manifestations (Axis 1) and etiology (Axis 2). An Axis 1 clinical syndrome is a recurring group of clinical symptoms, signs (physical findings), and possibly laboratory results that suggests the presence of at least one underlying Axis 2 etiology. Syndromes must be defined and used cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…However, this syndrome vs disease issue is controversial, and it is discussed in detail elsewhere. 12,13 A wide variety of conditions, that is, neurodegenerative, genetic, metabolic, toxin and drug exposures, infections, and structural brain lesions, may result in tremor, and such underlying conditions should be ruled out before labeling the tremor as ET. 1 The conditions that may present with isolated action tremor resembling that in ET are DT, SCA12, and DYT 24 (ANO3 variation).…”
Section: Clinical Assessment Of Et: the Changing Dynamicsmentioning
confidence: 99%
“…However, this syndrome vs disease issue is controversial, and it is discussed in detail elsewhere. 12,13 A wide variety of conditions, that is, neurodegenerative, genetic, metabolic, toxin and drug exposures, infections, and structural brain lesions, may result in tremor, and such underlying conditions should be ruled out before labeling the tremor as ET. 1 The conditions that may present with isolated action tremor resembling that in ET are DT, SCA12, and DYT 24 (ANO3 variation).…”
Section: Clinical Assessment Of Et: the Changing Dynamicsmentioning
confidence: 99%
“…Essential tremor was defined as an Axis 1 tremor syndrome with “isolated tremor syndrome of bilateral upper limb action tremor” of “at least 3 years’ duration” in the “absence of other neurological signs, such as dystonia, ataxia, or parkinsonism”. “Essential tremor plus” was adopted to describe tremor with the characteristics of ET as well as “additional neurological signs of uncertain significance” [ 1 ], in order to accommodate the additional movement disorders and non-motor symptoms increasingly described in ET patients [ 2 3 4 5 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These Axis 1 definitions, based on clinical features, and the division into isolated ET and ET plus have been challenged and have created controversy within the field [ 4 9 10 11 12 ]. Some studies have found that a majority of patients with a prior diagnosis of ET require reclassification from ET to ET plus [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic approach and conclusions that underlie the present manuscript are consonant with classical illness nosological principles, that is, syndromes such as POTS, Sjogren's syndrome, Tourette's syndrome, and essential tremor, for example, are defined as a recurring group of clinical symptoms, signs, and test results without a known etiology. [51][52][53] Inherent to these principles is that a defined syndrome is a waystation 51 -a "diagnostic placeholder"-on the scientific journey toward the discovery of specific etiologies and treatment. Thus, the diagnostic approach and identification of cutaneous alpha-synuclein in these patients could be considered a step toward the delineation of an etiology in a small subgroup of the heterogeneous postural tachycardia syndrome population.…”
Section: Discussionmentioning
confidence: 99%